Efficiency, Welfare, and Political Competition - Felix Bierbrauer; Pierre C. Boyer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study political competition in an environment in which voters have private information about their preferences. Our framework covers models of income taxation, public-goods provision or publicly provided private goods. Politicians are vote-share-maximizers. They can propose any policy that is resource-feasible and incentive-compatible. They can also offer special favors to subsets of the electorate. We prove two main results. First, in a symmetric equilibrium, policies are surplus-maximizing and hence first-best Pareto-efficient. Second, there is a surplus-maximizing policy that wins a majority against any welfare-maximizing policy. Thus, in our model, policies that trade off equity and efficiency considerations are politically infeasible.
Keywords: C72; D72; D82; H41; 330; political competition; asymmetric information; public goods; non-linear income taxation; redistributive politics